2000
DOI: 10.1007/bf02344869
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional mapping of brainstem functional lesions

Abstract: The human brainstem is a highly complex structure where even small lesions can give rise to a variety of symptoms and outward signs. Localising the area of dysfunction within the brainstem is often a difficult task. To make localisation easier, a neural net system has been developed which uses 72 clinical and neurophysiological data inputs to provide a display (using 5268 voxels) on a three-dimensional model of the human brainstem. The net was trained by means of a back-propagation algorithm, over a pool of 58… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 23 publications
0
5
0
1
Order By: Relevance
“…This is a voxel‐based three‐dimensional brainstem model15, 18, 22 developed using data from several topometric and stereotactic atlases21, 23, 24 (Fig 2). It is subdivided into 5,268 volume elements (“voxels”) ranging from 2 × 2 × 2mm to 2 × 2 × 4mm.…”
Section: Methodsmentioning
confidence: 99%
“…This is a voxel‐based three‐dimensional brainstem model15, 18, 22 developed using data from several topometric and stereotactic atlases21, 23, 24 (Fig 2). It is subdivided into 5,268 volume elements (“voxels”) ranging from 2 × 2 × 2mm to 2 × 2 × 4mm.…”
Section: Methodsmentioning
confidence: 99%
“…A group analysis would possibly create further insights into brainstem processing according to the progress in cortical neuroscience facilitated by appropriate fMRI techniques in the last decade. Some projects recently addressed that problem [6,14,31,36,40]; however, a gold standard is still missing. The present study demonstrated an algorithm of data processing that enables the projection of brainstem activity onto a standardized 3D space.…”
Section: Discussionmentioning
confidence: 99%
“…Given the anatomical–functional right–left symmetry of the brainstem, all left‐sided lesions were flipped to the right side, normalized, and imported into a three‐dimensional brainstem model1 based on data from topometric and stereotactic atlases 8, 13, 14. This idealized brainstem model was subdivided into 5268 volume elements (“voxels”) ranging from 2 × 2 × 2 mm to 2 × 2 × 4 mm.…”
Section: Methodsmentioning
confidence: 99%